Occupational Accident Risk Analysis in the Production Process of Barokah Furniture Industry Pasuruan Using FMEA (Failure Mode and Effect Analysis) and FTA (Fault Tree Analysis) Methods - Muhammad Ainur Rozaq Fadillah (Pasca Sarjana UKI, 2025)
This study aims to analyze occupational accident risks in the production process at Barokah Furniture Pasuruan using the Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods. The furniture industry involves various potential hazards in its production process, such as the use of cutting tools, dust exposure, and high-risk manual work techniques, necessitating a systematic evaluation to minimize workplace accidents. The FMEA method is used to identify and prioritize risks based on the Risk Priority Number (RPN), calculated from a combination of severity, occurrence, and detection. The analysis results identified 20 failure modes, with the three primary risks having the highest RPN: cuts from saw blades (RPN=250), respiratory issues due to excessive dust (RPN=196), and hand injuries from the use of manual planers and machine knives (RPN=180). Furthermore, a Fault Tree Analysis (FTA) was conducted to map the root causes of each priority failure mode. Based on the analysis, it was found that the main causes of workplace accidents at Barokah Furniture include the absence of safe working SOPs, lack of personal protective equipment (PPE), risky manual work techniques, and minimal control over dust hazards. Recommended improvements include the creation of written SOPs, provision of auxiliary tools and PPE, installation of dust extraction systems, and safety training for all employees. This research is expected to serve as a reference for the company to continuously improve its occupational safety and health systems.